THE EXISTENCE OF VIBRIO CHOLERAE IN INDONESIA: FROM ENVIRONMENTAL TO CLINICAL ASPECTS (A CONCISE REVIEW) - Rian Ka Praja; Anggita Ratri Pusporini; Reny Rosalina; I Wayan Muda Suta Arta; I Dewa Made Sukrama; Ni Nengah Dwi Fatmawati (OISAA, 2021)
Vibrio cholerae is an infectious agent causing cholera disease with a high prevalence in various developing countries. V. cholerae is a pathogen with broad spectrum host that can infect humans and animals, especially aquaculture. The existence of this disease in Indonesia has long been identified in several outbreaks. Various reports in Indonesia have succeeded in finding the existence of V. cholerae in the environment, aquaculture, food and beverage, as well as in clinical cases of V. cholerae infection. The presence of V. cholerae in environment such as water source is commonly related with contamination. However, V. cholerae can be found in aquatic environment as this environment is natural habitat for V. cholerae. Thus, aquaculture is prone to be infected with V. cholerae because the presence of this pathogen is abundant in aquatic environment. Contaminated food and beverage are associated with hygiene and sanitation and human is commonly infected after consuming contaminated food or beverage. This brief review has the main focus to discuss the existence of V. cholerae from environmental to clinical aspects found in Indonesia.